Haemato-biochemical Study of Canine Babesiosis in Anand, Gujarat - Bilwal, AK; Mandali, GC; Rao, Neha; Vasva, PR; Mahida, NR (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The aim of this study was to evaluate the haemato-biochemical alterations in dogs infected with canine babesiosis presented at the College clinics at Anand, Gujarat. Blood was collected with and without anticoagulant from naturally infected dogs, which were found positive for babesiosis by direct blood smear examination. Statistical analysis of affected (n=24) and healthy (n=8) dogs revealed significant decrease in the mean values of haemoglobin, total leucocyte count, packed cell volume, platelets and lymphocytes and significant increase in the mean values of neutrophils and eosinophils indicating anaemia, thrombocytopaenia, neutrophilia, lymphopenia and eosinophilia in infected dogs as compared to healthy ones. Similarly significant increase in the mean values of serum ALP, ALT, AST, globulin and BUN and decrease in albumin and A:G ratio were observed in infected dogs. The results showed significant alterations in haemato-biochemical attributes in dogs affected with canine babesiosis, and suggested need to rule out possibility of canine babesiosis in all anaemic dogs